2019
DOI: 10.1111/bph.14662
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Kv7 channels as a novel mechanism for NO/cGMP‐induced pulmonary vasodilation

Abstract: Background and Purpose The NO/cGMP pathway represents a major physiological signalling controlling tone in pulmonary arteries (PA), and drugs activating this pathway are used to treat pulmonary arterial hypertension. Kv channels expressed in PA smooth muscle cells (PASMCs) are key determinants of vascular tone. We aimed to analyse the contribution of Kv1.5 and Kv7 channels in the electrophysiological and vasodilating effects evoked by NO donors and the GC stimulator riociguat in PA. Experimental Approach Kv cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…The NO/cGMP pathway represents a key physiological signaling controlling tone in PAs, and drugs stimulating this pathway are used to treat PAH (Barnes and Liu, 1995), and drugs activating this pathway are used to treat pulmonary arterial hypertension. Recently, we have found that NO donors and riociguat, a stimulator of sGC used for the treatment of pulmonary arterial hypertension, enhance Kv7 current and induce membrane hyperpolarization in fresh isolated PASMCs contributing to pulmonary vasodilation (Mondejar-Parreño et al, 2019). Further, we identified Kv7.5 channels as a potential member of the Kv7 family targeted by these drugs.…”
Section: Pulmonary Hypertensionmentioning
confidence: 88%
See 4 more Smart Citations
“…The NO/cGMP pathway represents a key physiological signaling controlling tone in PAs, and drugs stimulating this pathway are used to treat PAH (Barnes and Liu, 1995), and drugs activating this pathway are used to treat pulmonary arterial hypertension. Recently, we have found that NO donors and riociguat, a stimulator of sGC used for the treatment of pulmonary arterial hypertension, enhance Kv7 current and induce membrane hyperpolarization in fresh isolated PASMCs contributing to pulmonary vasodilation (Mondejar-Parreño et al, 2019). Further, we identified Kv7.5 channels as a potential member of the Kv7 family targeted by these drugs.…”
Section: Pulmonary Hypertensionmentioning
confidence: 88%
“…As detailed above, different studies have provided evidence that treatment with Kv7 channel activators such as flupirtine, retigabine, or fasudil is beneficial in different pulmonary hypertension models (Morecroft et al, 2009;Duong-Quy et al, 2013;Sedivy et al, 2015;Zhang and Wu, 2017). In addition, Kv7 channel activation has been shown to contribute to the pulmonary vasodilating effect induced by drugs approved for the pulmonary hypertension treatment such as nitric oxide or riociguat (Mondejar-Parreño et al, 2019).…”
Section: Pulmonary Vasodilatorsmentioning
confidence: 95%
See 3 more Smart Citations